Violência, magia e técnica - Calazans, Diego Rodrigues Souto (2009)
The objective of this work is to understand the relation among violence, magic and technic, taking as a starting-point an hypothesis by René Girard about the real function of sacrificial mechanism as a form that society has to defend itself. Our research also seeks to trace new ways to comprehend the studied phenomena. Violence is approached since its ontological fundament till the core of its menace to social cohesion; we searched also the options human groups dispose to keep it under acceptable parameters. The institution of sacrifice in societies where there is not a sufficiently established penal system, as it presents to colective fury a comum target, personates a chance to avoid an endless cicle of vengeances, with catastrophical consequences. Even rites of passage and, especially, of cure refer to scapegoat mechanism. Magic, so, is taken in this work as an inexhaustive source of cathartical rites, that expurgate group from its intrinsic agressiveness, potentially disaggregative, reinforcing thus solidarity. Modern technic, on the other side, most of cases, instead of helping on violence deflection, has been instigating us to take it as an instrument, transforming it on a mere social engineering tool. However, violence did not just prove, once and again, being uncontrolable, but even it manipulated repeatedly the ones who tried to manipulate it. Modernity, whether through national States or their rival actors, is full of exemples. We opted to exemplify the principles of this dissertation through an analysis of the period in russian history known as Red Terror , when millions of human deaths were directly provoked by government actions. In the end, we present a possibility to control violence in modern societies.